Growing old in the Middle Ages : 'winter clothes us in shadow and pain' - Shahar, Shulamith (Routledge, 1997)
Shahar draws a comprehensive picture of medieval old age, describing how it was perceived by different groups in society. This timely overview is an invaluable contribution to the social history of the whole of medieval Europe.